Quantitatve and Qualitative Housing Problems in Akure, Ondo State of Nigeria - , Johnson Dele Matthew Victor (Archives of Current Research International, 2024)
The growth and emergence of developing cities as a result of the influx of people in search of greener pasture has adversely led to an acute shortage of housing in Nigerian urban cities. This study investigates the housing problems in the study area in accordance to the quantity and quality factors. Thus. a careful survey was carried out with the use of a structural questionnaire administered to the residents to evaluate basic housing problems and the efforts made by both the public and private sectors in the provision of housing in Akure, the capital city of Ondo State, Nigeria, as well as the conscious efforts made to solve the qualitative and quantitative housing problems confronting the ever-increasing population in search of better living conditions in urban cities. A total of three hundred (300) questionnaires were administered to obtain necessary information on the housing condition of the city. The collected data were analyzed with the use of systematic sampling techniques. The study shows that the demand for housing is higher than its supply, which shows that housing demand is at an alarming rate that has resulted in an acute shortage of housing in the study area.